Al-‘Alam, Jihad, Dzalim, dan Mustadh‘afin: Perempuan Memaknai Perlawanan terhadap Pencemaran PT. RUM Sukoharjo - Candraningrum, Dewi (MAARIF Institute, 2024)
Since 2017, the mothers of Nguter, affected by environmental pollution caused by PT. RUM in Sukoharjo, Central Java, have mobilized to voice their environmental protests through prayer circles and religious sermons, conducted from house to house as well as in mosques. Throughout this process, a transformation in the meaning of certain Qur’anic terminologies they employ has taken place, including dzalim, al-‘alam, jihad, and mustadh‘afin. The term dzalim, which was previously used to refer to those who oppress the Muslim community, has been redefined to denote PT. RUM and its affiliates, including lawyers and judges who have supported the company during legal proceedings. Environmental awareness has also increased, as reflected in the growing use of the term al-‘alam. Previously infrequent in local discourse due to the community’s access to clean air and water, this term has now become integral to the resistance narrative following the contamination of the air and the Gupit River by hydrogen sulfide (H2S) pollution. Similarly, the concept of jihad has been internalized through Surah Al-‘Ankabut (29:69) and is manifested in the resistance against environmental degradation, which is regarded as both a moral and spiritual obligation. Furthermore, the term mustadh‘afin, frequently appearing in religious sermons and protest activities, has been adopted by the mothers of Nguter to self-identify as an oppressed community due to the presence of the rayon factory. The meaning of this term has expanded from ‘the downtrodden’ to encompass those ‘whose rights have been taken away’ and ‘those whose inheritance has been stripped.’ This semantic shift illustrates how the community interprets ecological disaster and constructs a collective identity rooted in religious values as they struggle against environmental pollution.